Resposta :
Resposta:
- 287
Explicação passo-a-passo:
Calcule f(g(x))= substituindo g(x) no lugar de x
f(g(x))=2(5x+2)²-1
f(g(x))=2(5.2+2)²-1
f(g(x)=2(10+2)²-1
f(g(x))=2(12)²-1
f(g(x))=2(144)-1
f(g(x))=2.144-1
f(g(x))=288-1
f(g(x))=287
Resposta:
. 287
Explicação passo-a-passo:
.
. f(x) = 2x² - 1 e g(x) = 5x + 2
.
. f(g(x)) = f(5x + 2)
. = 2 . (5x + 2)² - 1
. = 2 . [(5x)² + 2 . 5x + 2 + 2²] - 1
. = 2 . (25x² + 20x + 4) - 1
. = 50x² + 40x + 8 - 1
. = 50x² + 40x + 7
x = 2 ==> 50 . 2² + 40 . 2 + 7 =
. 50 . 4 + 80 + 7 =
. 200 + 87 =
. 287
.
(Espero ter colaborado)
.